Immune checkpoint blockade for locally advanced or recurrent/metastatic cervical cancer: An update on clinical data - Song, Zhuo; Zou, Kun; Zou, Lijuan (Frontiers in Oncology, 2022)
Immunotherapy has shown great promise in the field of oncology, and recent clinical trials have illustrated that immune checkpoint blockade (ICB) is safe and effective at treating a range of tumor types. Cervical cancer (CC) is the fourth most common malignancy in women. However, first-line treatments for locally advanced cervical cancer (LACC) and recurrent/metastatic (R/M) CC have limited efficacy. Thus, it is necessary to explore new treatment approaches. The National Comprehensive Cancer Network (NCCN) currently recommends pembrolizumab, a programmed cell death protein 1 (PD-1) monoclonal antibody, as a first line therapy for individuals with R/M CC. This study reviews the progress of ICB therapy for LACC and R/M CC and describes the current status of the combination of ICB therapy and other therapeutic modalities, including radiotherapy, chemotherapy, targeted therapy, and other immunotherapies. The focus is placed on studies published since 2018 with the aim of highlighting novel CC-specific immunotherapeutic approaches and treatment targets.